Dondang sayang board game design / Athiera Hana Mohd Pidaus and Rafuzan Jaafar - Mohd Pidaus, Athiera Hana; Jaafar, Rafuzan (Kolej Pengajian Seni Kreatif (KPSK) UiTM Cawangan Melaka, 2023)
The Board Game Design project started with how every project starts, which is defining the problem. In the book Managing the Design Process Concept Development by Terry Lee Stone, this step is in the Preparation step in the Process of Design. The problem being how the awareness of Dondang Sayang has been decreasing from generation to generation. Director of the State Department of Culture and Arts (JKKN), Ezlina Alias acknowledged that the continuation of Dondang Sayang in the Peranakan community is now at a critical juncture. She said that not only is the issue of the absence of legacy connectors among the new generation, but the decreasing number of existing pioneers due to the passing of the dead is also troubling. (Utusan Malaysia, June, 2021). According to Utusan Malaysia, a report on June 6 2021, stated that, the oldest ethnic Chetti for Dondang Sayang public figure zin the state, G. Meenachi, 91years old, died at Melaka Hospital.